2011
DOI: 10.3390/f2020505
|View full text |Cite
|
Sign up to set email alerts
|

Preparing for and Responding to Disturbance: Examples from the Forest Sector in Sweden and Canada

Abstract: Abstract:Coping or adaptation following large-scale disturbance may depend on the political system and its preparedness and policy development in relation to risks. Adaptive or foresight planning is necessary in order to account and plan for potential risks that may increase or take place concurrently with climate change. Forests constitute relevant examples of large-scale renewable resource systems that have been directly affected by recent environmental and social changes, and where different levels of manag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Uncertainties stemming from climate models also limit findings about appropriate adaptation measures (Jönsson et al 2013). Nevertheless, climaterelated risk and adaptation has become a concern for at least some Swedish forest owners (Keskitalo et al 2011b). There is also evidence that Swedish forest owners are starting to take adaptive action ).…”
Section: Factors Shaping Individual Adaption To Climate Change Adaptamentioning
confidence: 99%
See 1 more Smart Citation
“…Uncertainties stemming from climate models also limit findings about appropriate adaptation measures (Jönsson et al 2013). Nevertheless, climaterelated risk and adaptation has become a concern for at least some Swedish forest owners (Keskitalo et al 2011b). There is also evidence that Swedish forest owners are starting to take adaptive action ).…”
Section: Factors Shaping Individual Adaption To Climate Change Adaptamentioning
confidence: 99%
“…In the case of forest owners, evidence exists that some of them in both Europe and elsewhere are starting to consider adaptive actions (Keskitalo et al 2011b;Blennow 2012). The scientific understanding about favourable conditions of individual engagement with adaptation, however, remains obscure as research points in different directions.…”
Section: Introductionmentioning
confidence: 99%
“…Thus far, however, adaptation research has only had limited success in promoting adaptation among policymakers (Westerhoff & Juhola 2010;O'Brien 2012;Klein & Juhola 2014) or forestry stakeholders (Keskitalo et al 2011;Ulmanen et al 2012). Governments and organizations seeking to promote adaptation learning and engagement have often focused on disseminating scientific information about climate change impacts and adaptive measures (CRED 2009), yet it has also been recognized that social barriers can limit the success of such strategies in changing perceptions and behaviours (Lorenzoni et al 2007;Adger et al 2009;Moser & Ekstrom 2010;Wibeck 2013).…”
Section: Introductionmentioning
confidence: 96%
“…Changes in current management practices may therefore be needed to effectively utilize the productive capacity of forest landscape, at the same time increasing its resilience against the adverse impact of extreme weather events (Lucash et al 2017). Previous studies on the impacts of climate change and its risk factors at the stand level have shown that storm damage can be mitigated by using adaptation strategies such as avoiding thinning and reducing rotation lengths, and by promoting the growth of stands with alternative tree species rather than Norway spruce monocultures (Keskitalo et al 2011;Wallentin and Nilsson 2014;Subramanian et al 2016a). In addition to protecting against storm damage, cultivating alternative species (as opposed to Norway spruce monocultures) improves biodiversity, increases resistance to root rot (Heterobasidion annosum [Fr.]…”
Section: Introductionmentioning
confidence: 99%